2020
DOI: 10.1093/humrep/deaa063
|View full text |Cite
|
Sign up to set email alerts
|

Exploring reproductive associations of serum polybrominated diphenyl ether and hydroxylated brominated diphenyl ether concentrations among women undergoing in vitro fertilization

Abstract: STUDY QUESTION Are serum concentrations of polybrominated diphenyl ethers (PBDEs) and hydroxylated brominated diphenyl ethers (OH-BDEs) associated with IVF endpoints? SUMMARY ANSWER Positive associations were observed for BDE153 and several OH-BDEs with IVF endpoints. WHAT IS KNOWN ALREADY PBDEs have been voluntarily phased out of production in the USA and EU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…Overall, the essential trace element concentrations that we observed in the FF and urine corroborate with previous findings [ 11 ], but the data presented herein evidenced that FF, and particularly, plasma, are more suitable for trace element screening and better for predicting intermediate reproductive outcomes than urine (where excess excretion needs to be considered). Similar to previous studies [ 14 , 15 , 16 ], we have observed that urine (reflecting essential trace element clearance) has a distinct metabolic signature than FF and plasma (which reflect essential trace element homeostasis), which could help explain the different associations observed for each biological fluid.…”
Section: Discussionsupporting
confidence: 88%
“…Overall, the essential trace element concentrations that we observed in the FF and urine corroborate with previous findings [ 11 ], but the data presented herein evidenced that FF, and particularly, plasma, are more suitable for trace element screening and better for predicting intermediate reproductive outcomes than urine (where excess excretion needs to be considered). Similar to previous studies [ 14 , 15 , 16 ], we have observed that urine (reflecting essential trace element clearance) has a distinct metabolic signature than FF and plasma (which reflect essential trace element homeostasis), which could help explain the different associations observed for each biological fluid.…”
Section: Discussionsupporting
confidence: 88%
“…Further, increased serum levels of PBDE congeners 17, 28, 66, and homolog triBDE were associated with increased risk of incident pregnancy loss (Choi et al, 2019 ). Conversely, opposite findings were observed in a later study where increased serum levels of BDE 153 and OH‐BDE metabolites were associated with an increased probability of implantation, clinical pregnancy, and live birth, suggesting a potential protective effect (Ingle et al, 2020 ). Interestingly, racial disparities may exist when considering the impact of PBDE exposures and female reproductive health.…”
Section: Flame Retardantsmentioning
confidence: 87%
“…Interestingly, racial disparities may exist when considering the impact of PBDE exposures and female reproductive health. When stratified by race, these positive correlations remain for white women; however, increases in all PBDEs and metabolites tended to decrease all IVF outcomes in non‐white women, with a significant association between BDE 47 and decreased probability of clinical pregnancy being observed (Ingle et al, 2020 ). In this study, the levels of PBDEs and OH‐BDEs were higher in non‐white women when compared to white women, which is consistent with findings in the literature.…”
Section: Flame Retardantsmentioning
confidence: 99%
“…Ingle, Mínguez‐Alarcón, Carignan, Stapleton, Williams, Ford, Moravek, Hauser, and Meeker ( 2020 ) reporting on the Environmental and Reproductive Health (EARTH) Study in the USA ( n = 215 women, 330 in vitro fertilisation (IVF) cycles) investigated the association between PBDE levels preconceptionally in women. Five PBDE congeners were analysed ( BDE‐47 , ‐ 99 , ‐ 100 , ‐ 153 , ‐ 154 ) and 4 OH‐PBDEs (3‐OH‐BDE‐47, 5‐OH‐BDE‐47, 6‐OH‐BDE‐47, 4‐OH‐BDE‐49) and IVF‐related endpoints (total oocyte yield, M2 oocyte yield, endometrial wall thickness and fertilisation rate, implantation, clinical pregnancy and live birth).…”
Section: Assessmentmentioning
confidence: 99%
“…Regarding OH‐PBDEs, as discussed above, Ingle, Mínguez‐Alarcón, Carignan, Stapleton, Williams, Ford, Moravek, Hauser, and Meeker ( 2020 ) for the EARTH study focused on IVF‐related endpoints. Due to coelution occurrence, 3‐OH‐BDE‐47 and 5‐OH‐BDE‐47 were presented individually and combined.…”
Section: Assessmentmentioning
confidence: 99%